Systematic review: The gut microbiota as a link between colorectal cancer and obesity - Ruiz‐Malagón, Antonio Jesús; Rodríguez‐Sojo, María Jesús; Redondo, Eduardo; Rodríguez‐Cabezas, María Elena; Gálvez, Julio; Rodríguez‐Nogales, Alba (Obesity reviews, 2025)
Summary Microbiome modulation is one of the novel strategies in medicine with the greatest future to improve the health of individuals and reduce the risk of different conditions, including metabolic, immune, inflammatory, and degenerative diseases, as well as cancer. Regarding the latter, many studies have reported the role of the gut microbiome in carcinogenesis, formation and progression of colorectal cancer (CRC), as well as its response to different systemic therapies. Likewise, obesity, one of the most important risk factors for CRC, is also well known for its association with gut dysbiosis. Moreover, obesity and CRC display, apart from microbial dysbiosis, chronic inflammation, which participates in their pathogenesis. Although human and murine studies demonstrate the significant impact of the microbiome in regulating energy metabolism and CRC development, little is understood about the contribution of the microbiome to the development of obesity‐associated CRC. Therefore, this systematic review explores the evidence for microbiome changes associated with these conditions and hypothesizes that this may contribute to the pathogenesis of obesity‐related CRC. Two databases were searched, and different studies on the relationship among obesity, intestinal microbiota and CRC in clinical and preclinical models were selected. Data extraction was carried out by two reviewers independently, and 101 studies were finally considered. Findings indicate the existence of a risk association between obesity and CRC derived from metabolic, immune, and microbial disorders.